Islamic Economists in The Early 21st Century Viewâs on Business Ethics - Hakim, Rahmad (FALAH Jurnal Ekonomi Syariah, 2016)
Islamic Economists in The Early 21st CenturyViewâs on Business EthicsRahmad HakimProgram Studi Ekonomi Syariah, Fakultas Agama Islam,Universitas Muhammadiyah MalangE-mail: rahmadhakiem@gmail.comABSTRACTThe focus of this study is to determine several thoughts of Islamic Economist of the early 21st Century related on business ethics through their works in Islamic Economics, especially in business ethics. In order to find the deeper and more comprehensive research, The researcher limited this research only to four Islamic Economists of the early 21st Century, such as; M. Umer Chapra, Syed Nawab Haider Naqvi, Mohamed Ariff, Akram Khan. The conclusion of this study are as follows: first, the Muslim economists trying to solve problems that occur particularly in the case of dichotomies in the fulfillment of material needs and non-material need, although there are some flaws. Second, Muslim economists at least try to realize human well-being based on Islamic principles. Third, the Muslim economists are also tried to build the Islamic ethics as a discipline that was not present before.Keywords: Islamic Economist, Business Ethics, Islamic Business